Factibilidad para la creación de una sucursal de la Ferretería Domínguez en el cantón Quinsaloma, período 2012 - Coello Aguirre, Mayra Jessenia (2013)
The research was conducted in the canton Quinsaloma, whose boundaries are the North with the Canton La Maná, on the south by the parish Zapotal - Canton windows and on the east by the parish Moraspungo - Pangua canton and the following geographical coordinates 1 ° 00 " South latitude and 79 ° 25 'west longitude, at an altitude of 168 meters, with a duration of 210 days, had the following objectives: a) Conduct a feasibility study for the establishment of a branch in the corner hardware store Quinsaloma Dominguez, period 2012, b) diagnosed by a market study the need for the establishment of a branch in the corner hardware store Quinsaloma Dominguez, period 2012 c) Develop a technical and economic study to determine the investment needed for the project, d) Determine the financial feasibility of this study for the establishment of a branch in the corner hardware store Quinsaloma Domínguez, 2012. The methodology used was scientific, the target population of 6283 inhabitants are canton Quinsaloma of the economically active population, according to INEC 2010 with a population growth of 1.21%, the sample of the survey population is 342 people for determine demand, which was considered to owners of premises where sold hardware products to meet the supply of products. By studying market demand is met building materials, electrical, tools and among others in the canton Quinsaloma, province of Los Ríos, requires a fixed investment of 44.396.95 dollars themselves that require funding of 35 % over two years and the difference will be from own resources. In the first year of income is $ 117,600, while the financial study shows an NPV of 300.681,43 dollars, 118.28% IRR and Benefit Cost Ratio of 1.75%, ie recovering a 0.75 dollar cents, demonstrating the viability of the project from the point of view of the financial evaluation and market research, this is demonstrated with the hypothesis that investment for this type of business is profitable and feasible.